Effects of auditory training on children with developmental language disorder: a systematic review - Hu, Wenxin; Zhang, Jialin; Chen, Tao; Sun, Yuying (Frontiers in Human Neuroscience, 2025)
ObjectiveThis systematic review aims to evaluate the effectiveness of auditory training (AT) on various parameters, including language abilities, speech perception, auditory behavior, electrophysiological assessments, and working memory, in children with developmental language disorder (DLD) population.MethodsWe searched PubMed, Web of Science, EMBASE, MEDLINE, Cochrane Library and CINAHL from inception to August 7, 2023, and further scrutinized the references of all selected articles. We included randomized controlled trials (RCTs) and quasi-experimental studies that investigated the effects of AT on children with DLD. Two researchers independently screened studies, extracted data and assessed risk of bias.ResultsWe included nine studies (eight RCTs and one quasi-experimental) in the systematic review, encompassing 379 children with DLD, 195 in the AT group and 184 in the control group. Compared to controls across five studies, AT did not significantly increase language abilities (expressive, receptive and total). Four out of five studies found significant improvements in children’s speech perception abilities after AT treatment, particularly phonological awareness and phoneme discrimination. Two studies showed improvements in temporal ordering and figure-context assessment, but two other studies found no significant changes. Two studies examining electrophysiological measures reported increased amplitudes in auditory event-related potentials after AT. Results for phonological working memory were inconsistent, with one study showing improvements in non-word repetition and digit span tasks, while another found no significant changes.ConclusionCurrent evidence does not support the effectiveness of AT in enhancing core language abilities in children with DLD. However, AT may offer potential benefits for specific auditory processing skills and speech perception. More precise evaluation of the effectiveness of AT therapies in this population should be conducted in future research by employing rigorous methodology, bigger sample numbers and standardized outcome measures.Systematic review registrationwww.crd.york.ac.uk/PROSPERO/myprospero, identifier CRD42024583480.